Home and away: the use of institutional and non-institutional technologies to support learning and teaching. Issue 7 (2nd October 2016) - Flavin, Michael
Abstract : This paper examines the usage of institutional and non-institutional technologies to support learning and teaching in UK higher education. Previous work on disruptive technology and disruptive innovation has argued that users prefer simple and convenient technologies, and often repurpose technologies from designers' intentions; this paper evaluates its data in relation to this argument. The paper uses a structured observation as its research instrument; seven participants (three lecturers and four students) were given one of two tasks. Results showed the participants using a narrow range of technologies, and showed a preference for non-institutional over institutional technologies. The paper argues that there is a misalignment between the technologies provided by higher education institutions (HEIs) and the technologies used in practice by students and lecturers, and further argues that disruptive technology and disruptive innovation comprise a useful means of assessing the likely success, in terms of usage, of a technology.